ASPEK KERJASAMA DALAM KETERAMPILAN SOSIAL SISWA KELAS IV SEKOLAH DASAR - Eka Kurnia Wati; Endang Sri Maruti; Melik Budiarti (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2020)
Cooperation is a relationship made by two or more people who have the goal to carry out an activity together with those who have the same goals for the common good. Be an explanation of cooperation on that really needs to be instilled and developed in students, because by supporting the training of fourth grade students at MI Kinandang able to create and support competition, interpersonal communication, build and trust, and improve relationships in learning that is opened and transitioned. In cooperation skills, students learn firsthand about social skills which is a collaboration of one of social skills. Because social skills are very important for fourth grade students because students will be individuals who can behave in accordance with their social environment, so that students can be accepted into the environment or group. More than just students who have social problems that are not good, it can be done by students in relationships with the environment associated with collaborative activities.